The factors that attracted the scholars of the Levant to come to Baghdad (Journal of the College of Basic Education, 2023)
This study aims at "the factors that attracted the scholars of the Levant to come to Baghdad ," as Baghdad became the capital of the Abbasid Caliphate , which made scholars flock to it from all sides, as the intellectual, scientific and cultural movement was active during this period, and in this study we shed light on a historical overview about Introducing the Levant region, as well as reviewing the factors that contributed to attracting Levantine scholars to Baghdad, and the nature of their arrival and residence there.